2024
DOI: 10.1111/1751-7915.14435
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces‐triggered coordination between rhizosphere microbiomes and plant transcriptome enables watermelon Fusarium wilt resistance

An‐Hui Ge,
Qi‐Yun Li,
Hong‐Wei Liu
et al.

Abstract: The use of microbial inoculant is a promising strategy to improve plant health, but their efficiency often faces challenges due to difficulties in successful microbial colonization in soil environments. To this end, the application of biostimulation products derived from microbes is expected to resolve these barriers via direct interactions with plants or soil pathogens. However, their effectiveness and mechanisms for promoting plant growth and disease resistance remain elusive. In this study, we showed that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Streptomyces can significantly promote the inhibition of crop diseases. A recent study showed that Streptomyces ahygroscopicus strain 769, which belongs to Streptomyces, can significantly reduce the incidence of Fusarium wilt of watermelons and increase the biomass of plants [35]. In our study, Streptomyces was a microbial genus with significant differences between groups selected via LEfSe analysis.…”
Section: Discussionmentioning
confidence: 62%
“…Streptomyces can significantly promote the inhibition of crop diseases. A recent study showed that Streptomyces ahygroscopicus strain 769, which belongs to Streptomyces, can significantly reduce the incidence of Fusarium wilt of watermelons and increase the biomass of plants [35]. In our study, Streptomyces was a microbial genus with significant differences between groups selected via LEfSe analysis.…”
Section: Discussionmentioning
confidence: 62%